Measuring Contemporary Islamic Banking Sustainability: Integrating ESG and Maqashid al-Syarī‘ah in Indonesia - Edian Fahmy; Muhamad Nadratuzzaman Hosen; Titi Dewi Warninda; Ali Rama; Qeis Aimar (MILRev: Metro Islamic Law Review, 2026)
The measurement of sustainability in Islamic banking in Indonesia remains largely dominated by conventional Environmental, Social, and Governance (ESG) frameworks, which tend to emphasize formal compliance and value-neutral indicators. Such approaches have not fully captured the ethical and normative dimensions embedded in Islamic finance. This study aims to formulate a comprehensive model for measuring the sustainability of contemporary Islamic banking by integrating ESG principles with Islamic value-based sustainability indices, namely the Islamic Corporate Sustainability Practices Index (ICSPI), Islamic Banking Sustainability Performance Index (IBSPI), and Maqāṣid Sharī‘ah Index (MSI). This research employs a mixed-methods approach. The Analytic Network Process (ANP) is utilized to identify and prioritize the most relevant sharia-based sustainability index based on stakeholder perspectives. Furthermore, Structural Equation Modeling–Partial Least Squares (SEM-PLS) is applied to examine the impact of ESG integration and Sharia sustainability models on the financial performance of Islamic banks, as proxied by Return on Assets (ROA) and Return on Equity (ROE). The findings reveal that integrating ESG with a maqāṣid al-sharī‘ah-based sustainability index provides a more holistic and substantive framework for assessing sustainability in Islamic banking. This integrated model not only enhances measurement accuracy but also aligns financial performance with ethical and social objectives rooted in Islamic principles. This study contributes to the advancement of contemporary Islamic economic law by offering a conceptual framework that bridges conventional sustainability metrics with Islamic normative values. Additionally, it provides practical implications for policymakers and industry practitioners in developing more robust, value-oriented sustainability standards within the Islamic banking sector.